2006
DOI: 10.1002/tox.20203
|View full text |Cite
|
Sign up to set email alerts
|

Brain and gonadal aromatase as potential targets of endocrine disrupting chemicals in a model species, the zebrafish (Danio rerio)

Abstract: Many chemicals in the aquatic environment are able to adversely affect in vitro brain and ovarian aromatase expression/activity. However, it remains to be determined if these substances elicit in vivo effect in fish. With the view to further understanding possible effects of endocrine disrupting chemicals (EDCs) on aromatase function, we first developed methods to measure brain and ovarian aromatase expression/activity in a model species, the zebrafish, and assessed the effect of estradiol (E2) and androstatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 31 publications
11
36
1
Order By: Relevance
“…This is in perfect agreement with the fact that cyp19a1b expres-sion in the brain of developing and adult fish which is restricted to radial glial cells (Forlano et al, 2001;Menuet et al, 2003Menuet et al, , 2005Strobl-Mazzulla et al, 2005, 2008Kallivretaki et al, 2007;Pellegrini et al, 2007). Because of this high sensitivity to estrogens, cyp19a1b is a target for certain endocrine disrupters (EDs) with estrogenic activities (Cheshenko et al, 2008) and many recent studies have highlighted the effects on recognized estrogenic EDs on cyp19a1b expression either in vivo or in vitro (Melo and Ramsdell, 2001;Halm et al, 2002;Hinfray et al, 2006;Le Page et al, 2006, 2008Lee et al, 2006;Lassiter and Linney, 2007).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in perfect agreement with the fact that cyp19a1b expres-sion in the brain of developing and adult fish which is restricted to radial glial cells (Forlano et al, 2001;Menuet et al, 2003Menuet et al, , 2005Strobl-Mazzulla et al, 2005, 2008Kallivretaki et al, 2007;Pellegrini et al, 2007). Because of this high sensitivity to estrogens, cyp19a1b is a target for certain endocrine disrupters (EDs) with estrogenic activities (Cheshenko et al, 2008) and many recent studies have highlighted the effects on recognized estrogenic EDs on cyp19a1b expression either in vivo or in vitro (Melo and Ramsdell, 2001;Halm et al, 2002;Hinfray et al, 2006;Le Page et al, 2006, 2008Lee et al, 2006;Lassiter and Linney, 2007).…”
Section: Introductionsupporting
confidence: 80%
“…This assumption is reinforced by the fact that treatment of control embryos with ICI causes a strong reduction in cypa19a1b basal expression at all time points suggesting that basal expression relies in large part upon activation of estrogen receptors. We and others have previously shown that the cyp19a1b gene is very sensitive to E2 in young and adult fish (Hinfray et al, 2006;Sawyer et al, 2006;Cheshenko et al, 2007;Lassiter and Linney, 2007;Cheshenko et al, 2008;Le Page et al, 2008;Marlatt et al, 2008;Mouriec et al, 2008;Strobl-Mazzulla et al, 2008 , cyp19a1b mRNAs remained undetectable in the brain using whole-mount in situ hybridization at all these early stages. Nevertheless, as already documented Mouriec et al, 2009), treating zebrafish embryos with E2 causes a dramatic increase in cyp19a1b expression that becomes detectable at the messenger level by in situ hybridization or protein level by immunohistochemistry as early as 32-36 hpf (data not shown).…”
Section: Early Cyp19a1b Expression Relies On Estrogen Receptorsmentioning
confidence: 66%
“…However, the relationship between aromatase activity and CYP19A1 or CYP19A2 mRNA expression in the same brain samples had not been previously tested in fish. The positive correlation between brain CYP19A2 mRNA expression and aromatase activity found in this study, together with the fact that in the fish brain the CYP19A2 gene expresses much more than the CYP19A1 gene (e.g., Hinfray et al, 2006;Kishida and Callard, 2001;Villeneuve et al, 2006), suggests that CYP19A2 mRNA expression levels provide a good indication of the potential for aromatization in the S. pavo brain.…”
Section: Discussionsupporting
confidence: 60%
“…Although we were unable to measure P450 aromatase activity, several previous studies with teleosts including zebrafish have shown that mRNA levels of cyp19 are correlated well with aromatase activity (Fukada et al, 1996;Chang et al, 1997;Hinfray et al, 2006). In this aspect, several previous reports have also shown that the inhibition of the aromatase cyp19 gene can reduce estradiol production, leading to an increase in the ratio of androgens to estrogens, and finally affecting the sex ratio (Guiguen et al, 2010;Shang et al, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…In fish, the outcome of this process (i.e., the development of a testis or an ovary) is regulated by the androgen: estrogen ratio, which is controlled by aromatase (Devlin and Nagahama, 2002). It is well known that the cyp19 gene expression and aromatase activity are very sensitive to xenoestrogens in zebrafish and have been used as promising molecular and biochemical markers of endocrine disrupting chemicals in fish (Hinfray et al, 2006;Menuet et al, 2005). Fenske and Segner (2004) reported that the suppression of aromatase activity (administrated by the aromatase inhibitor fadrozole) induced male gonadal sex differentiation.…”
Section: Discussionmentioning
confidence: 99%